A centralized reactive power compensation system for LV distribution networks - Chen, Shuai Xun (2015)
A centralized reactive power compensation system is proposed for low voltage (LV) distribution networks. It can be connected with any bus which needs reactive power. The current industry practice is to locally install reactive power compensation system to maintain the local bus voltage and power factor. By centralizing capacitor banks together, it can help to maintain bus voltages and power factors as well as reduce the power cable losses. Besides, the centralized reactive power system can be easily expanded to meet any future load increase. A reasonably sized centralized reactive power compensation system will be capable of meeting the requirements of the network and the optimization algorithm proposed in this paper can help to find this optimal size by minimizing the expected total cost (ETCH). Different load situations and their respective probabilities are also considered in the proposed algorithm. The concept of the centralized reactive power compensation system is applied to a local shipyard power system to verify its effectiveness. The results show that an optimally sized centralized reactive power system exists and is capable of maintaining bus voltages as well as reducing the power losses in the distribution network. A significant power loss reduction can be obtained at the optimal capacity of the centralized reactive power compensation system in the case study.